Sexting or pedophilia? = ¿Sexteo o pedofilia? = ¿Mensagens de texto sexuais ou pedofilia? - Kaur, Prit (Revista Criminalidad, 2014)
The scholarly world is seriously debating the critical need for some legal statutes or legislation helping to establish a differentiation between sexual images and contents usually created and shared by teenagers and young adults through mobile phones and what is known today as cyber porn, a new method developed by pedophiles using the internet as a means to sexually harass and exploit children. This paper, mainly based on secondary analyses, includes empirical research conducted on 13 police officers, 20 teenagers, and 20 parents of teenagers. It reveals the severity of the situation and emphasizes the urgency for an immediate and appropriate legal response.